STRATEGI HUMAS LAZIS AL IHSAN DALAM MENARIK MUZZAKI MELALUI PROGRAM SEDEKAH SUBUH - Irvan, Irvan Afrizal Pratama (Prodi Ilmu Komunikasi Universitas Sahid Surakarta, 2023)
Lazis Al Ihsan Surakarta has zakat and alms fundraising program, namely the sedekah subuh program. ThisProgram aims to provide a forum for muslims in Surakarta to distribute zakat, infaq, and alms funds. This studyused descriptive qualitative research with data collection methods of interviews and documentation. The studyaimed to explain Lazis Al Ihsan's public relation strategy for attracting muzzaki through the sedekah subuhprogram. The results were that the strategy carried out by Lazis Al Ihsan Surakarta in attracting muzzaki throughthe sedekah subuh program used 4 (four) steps, namely fact finding, and feedback carried out by Lazis Al IhsanSurakarta to find facts before conducting socialization, planning, and programming to determine steps to betaken before carrying out socialization, action, and communication to carry out socialization activities for thesedekah subuh program. Lazis Al Ihsan Surakarta conducted socialization through various media such as socialmedia (official website, radio broadcasts, WhatsApp) and print media (flyers, brochures). Evaluation was carriedout every three months by Lazis Al Ihsan by collecting the relevant coordinators.